1995
DOI: 10.1002/app.1995.070570309
|View full text |Cite
|
Sign up to set email alerts
|

High‐impact poly(ethylene terephthalate) blends

Abstract: SYNOPSISRubbers of different kind were tested as toughening agents of poly(ethy1ene terephthalate) (PET), noting significant morphological and mechanical differences. In particular, good results were obtained by using an ethylene-ethyl acrylate-glycidyl methacrylate copolymer. The resulting blend evidenced good particle distribution, and the latter was related to chemical interactions between the rubber epoxy groups and PET terminal groups, including the effect of low molecular weight and polymeric amine catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…The absence of the two absorption bands (at 1945, 1873 cm −1 ) of maleic anhydride group in SEBS-g-MA for both compatibilized LCP-and rPET-composites is observed, indicating the interaction between maleic anhydride groups of SEBS-g-MA with the hydroxyl end-group of PET component [22,25,26]. The interaction between carbonyl groups of PET and SEBS-g-MA from FTIR studies has also been proved by Carte et al [27] and Penco et al [28].…”
Section: Ftir Characterizationsupporting
confidence: 64%
“…The absence of the two absorption bands (at 1945, 1873 cm −1 ) of maleic anhydride group in SEBS-g-MA for both compatibilized LCP-and rPET-composites is observed, indicating the interaction between maleic anhydride groups of SEBS-g-MA with the hydroxyl end-group of PET component [22,25,26]. The interaction between carbonyl groups of PET and SEBS-g-MA from FTIR studies has also been proved by Carte et al [27] and Penco et al [28].…”
Section: Ftir Characterizationsupporting
confidence: 64%
“…[1][2][3][4] The triblock copolymers in these studies had styrene end blocks and an ethylene/butylene midblock (SEBS) that was grafted with maleic anhydride. Improved properties with these and other blends of PET that incorporated functionalized polymers [5][6][7][8] were consistent with in situ formation of a graft copolymer by reaction with PET end groups. It appeared that the graft copolymer acted as an emulsifier to decrease the interfacial tension and promote adhesion.…”
Section: Introductionmentioning
confidence: 61%
“…Akkapeddi et al 6,7) reported a significant improvement in toughness and heat resistance of the PET/HDPE (1.8 : 1 wt.-%) blends at a 10 wt.-% E/ GMA level compared to the uncompatibilized blend. Penco et al 8) have shown that the impact properties of PET can be improved by adding an ethylene/ethyl acrylate/glycidyl methacrylate terpolymer (E/EA/GMA). These good results are related to chemical interactions between the compatibilizer reactive groups (epoxides) and PET end groups (carboxyls and hydroxyls).…”
Section: Introductionmentioning
confidence: 99%